A STUDY ON THE CHALLENGES FOR MICRO FINANCE ORGANIZATION - YASHWANT KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
In recent years, in addition to Self-Help Groups and Linkage Programs, Bihar has seen the introduction of institutional microfinance institutions. This development took place in Bihar. NIDAN was the pioneering microfinance organization that was established in the state of Bihar when it initially began operations. In Bihar, it was based on the savings and loan association (SHG) and cooperative methods of microfinance. NIDAN was initially established as a loosely organised group with the goal of empowering young people, both male and female, to achieve financial autonomy through the provision of financial resources, as well as the provision of appropriate training and development facilities for the purpose of putting those resources to work. Since 1995, NIDAN has been officially registered as a society under the Societies Act, and it has been doing business in the following five districts of the state of Bihar: Patna, Vaishali, Katihar, Samastipur, and Muzaffarpur.